1999
DOI: 10.1038/sj.bmt.1701967
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclasses and avidity of antibodies to polysaccharide antigens in allogeneic BMT recipients after vaccination with pneumococcal polysaccharide and Haemophilus influenzae type b conjugate vaccines

Abstract: Summary:In a randomized study, 20 adult allogeneic BMT recipients were vaccinated at 6 months and 22 at 18 months after BMT with Streptococcus pneumoniae (Pnc) is the main cause of serious bacterial infections in allogeneic BMT recipients who survive Ͼ3 months after transplantation. [1][2][3][4][5] Haemophilus influenzae is also a significant cause of infections among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
(42 reference statements)
1
7
0
1
Order By: Relevance
“…5 Children given pneumococcal polysaccharide vaccines had shortlived responses of low avidity 22 in contrast to adults in Table 2 Summary of the EBMT vaccination recommendations whom the avidity was high. 23 There is no advantage in vaccinating the donor. In autologous SCT recipients, the response to a single dose of pneumococcal polysaccharide vaccine is poor regardless of the stem cell source 5,9 and remains decreased for several years after transplantation for lymphoma as compared to controls.…”
Section: Ebmt Vaccination Recommendations P Ljungman Et Almentioning
confidence: 99%
“…5 Children given pneumococcal polysaccharide vaccines had shortlived responses of low avidity 22 in contrast to adults in Table 2 Summary of the EBMT vaccination recommendations whom the avidity was high. 23 There is no advantage in vaccinating the donor. In autologous SCT recipients, the response to a single dose of pneumococcal polysaccharide vaccine is poor regardless of the stem cell source 5,9 and remains decreased for several years after transplantation for lymphoma as compared to controls.…”
Section: Ebmt Vaccination Recommendations P Ljungman Et Almentioning
confidence: 99%
“…This class of immunoglobulins consists of four subclasses, each encoded by a separate C-region gene and endowed with unique biological functions that are important for an efficient humoral response to a given pathogen. Recently it was demonstrated that antibody responses to viral protein antigens mainly are restricted to IgG1, IgG3, or both (3,5,6,9); IgG2 generally is stimulated by carbohydrate antigens (12,15), whereas IgG4 most likely reflects chronic antigen stimulation (13). Therefore, the monitoring of specific IgG subclass profiles after vaccination, compared with natural virus infection, may give an insight into the mechanisms that drive antibody production in both conditions.…”
mentioning
confidence: 99%
“…Почему же тогда у маленьких детей, несмотря на большое количество В1-лимфоцитов, в кро-ви определяются буквально следы IgA? По-видимому, это связано с тем, что плазматические клетки, производные от В1-лимфоцитов, распо-ложены в основном в слизистых и синтезируют львиную долю секреторных IgA [12] [8,11], IgG2-антитела стимулируются углеводными антигена-ми [17], тогда как IgG4, наиболее вероятно, игра-ют важную роль при хронической антигенной стимуляции [18,19]. Однако все не так просто.…”
Section: Discussionunclassified